Cell-Mediated Therapies to Facilitate Operational Tolerance in Liver Transplantation - Ellias, Samia D. (Int J Mol Sci, 2021)
Cell therapies using immune cells or non-parenchymal cells of the liver have emerged as potential treatments to facilitate immunosuppression withdrawal and to induce operational tolerance in liver transplant (LT) recipients. Recent pre-clinical and clinical trials of cellular therapies including regulatory T cells, regulatory dendritic cells, and mesenchymal cells have shown promising results. Here we briefly summarize current concepts of cellular therapy for induction of operational tolerance in LT recipients.